Pneumococcal antibody protection in patients with autoimmune inflammatory rheumatic diseases with varying vaccination status. (2nd September 2020) - Rasmussen, SL; Fuursted, K; Nielsen, KA; Laurberg, NP; Sørensen, MB; Fagerberg, SK; Leutscher, P; Rasmussen, C
Abstract : Objectives : The aims of this cross-sectional study were to assess the pneumococcal antibody coverage in patients with autoimmune inflammatory rheumatic disease (AIRD) and to identify predictors associated with inadequate protective antibody levels. Method : Antibodies to 12 serotypes occurring in the commonly applied pneumococcal vaccines in Denmark were measured in AIRD patients with a diagnosis of rheumatoid arthritis, spondyloarthritis, or psoriatic arthritis attending the Department of Rheumatology at the North Denmark Regional Hospital. Immunization against pneumococcal infection was defined as a geometric mean level ≥ 1 μg antibodies/mL. Clinical information about vaccination status and disease/treatment history was retrieved from the medical file system. Results : Results of antibody measurement and vaccination status were available from 346 AIRD patients, of whom 200 (58%) were registered as receiving pneumococcal vaccination, whereas the remaining 146 patients (42%) were not. Of all 346 patients, only 61 (18%) were measured with an adequate level of protective antibodies (30% vs 1%, respectively). Methotrexate treatment at the time of vaccination and increasing age were identified as predictors of poor vaccination outcome in multiple logistic regression analysis. Conclusions : This post-vaccination study showed that less than one-fifth of the AIRD patients are adequately protected against pneumococcal infection, although the immunization programme had been implemented in more than half of the study population. Development of improved vaccination strategies is required to achieve a higher immunization coverage rate and more efficient lasting antibody response.